Spread Spectrum Communications Handbook, Electronic Edition - Simon, Marvin K.; Omura, Jim K.; Scholtz, Robert A.; Levitt, Barry K. (McGraw-Hill Education, 2002)
Spread-spectrum systems have found important commercial applications in CDMA cellular networks and wireless personal communication networks. Communications engineers and technicians now have ready access to a wealth of spread-spectrum information in this exhaustive handbook the most comprehensive and authoritative compendium on spread-spectrum systems available anywhere. Written by recognized authorities in the field, the Handbook presents both theoretical basics and practical applications, providing succinct, results-oriented solutions to engineering problems.Starting with basic concepts and system models, the book covers: Anti-jamming communication systems; Coherent direct-sequence systems; Non-coherent frequency-hopped systems; Coherent and differentially coherent modulation techniques; Pseudonoise acquistion and tracking in direct sequence receivers; Time and frequency synchronization of frequency-hopped receivers; and, Low probability of intercept communications. In addition, it offers an in-depth look at multiple access communications and positioning systems and discusses the growth of spread-spectrum applications.